Evaluating The Efficacy of MGSO4 as an Adjuvant to 0.5% Bupivacaine in Supraclavicular-Intercostobrachial Nerve Blocks for Upper Extremity Hemodialysis Vascular Access Surgery - Albert, Albert; Senapathi, Tjokorda Gde Agung; Sucandra, I Made Agus Kresna (Green Publisher Indonesia, 2025)
Magnesium sulfate (MgSO₄) has garnered increasing attention as an adjunct to regional anesthesia, particularly for patients with compromised kidney function requiring upper limb surgery for hemodialysis access. While peripheral nerve blocks are commonly selected for their safety and efficacy in such populations, their delayed onset of action can pose a clinical drawback. To address this issue, a randomized clinical study was conducted at RSUP Prof. I.G.N.G. Ngoerah to investigate the benefits of adding 200 mg of 20% MgSO₄ to supraclavicular-intercostobrachial nerve blocks. A total of 28 participants were randomized into two groups: one receiving the magnesium additive and another as a control. The study assessed onset time for full sensory and motor block as well as analgesia duration. Results indicated that patients in the MgSO₄ group experienced faster sensory (average 10.08 minutes) and motor block onset (average 17.98 minutes), compared to the control group (17.19 and 25.19 minutes, respectively). Moreover, the duration of pain relief was substantially extended in the MgSO₄ group, exceeding 470 minutes on average. Secondary observations also revealed a lower intraoperative requirement for fentanyl and a potential regulatory effect on inflammation-related biomarkers, such as neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios. Overall, the findings suggest that MgSO₄ can serve as a valuable and safe enhancer of nerve block performance, especially in vulnerable surgical populations.